[(NHC)CoR2]: pre-catalysts for homogeneous olefin and alkyne hydrogenation. Issue 98 (26th November 2018) - Enachi, Andreea; Baabe, Dirk; Zaretzke, Marc-Kevin; Schweyen, Peter; Freytag, Matthias; Raeder, Jan; Walter, Marc D.
Abstract : [(I t Bu)Co(CH2 SiMe3 )2 ] serves as an efficient, homogeneous olefin hydrogenation catalyst. Abstract : A novel synthesis for dialkyl cobalt compounds [(tmeda)CoR2 ] is presented. In these complexes tmeda is readily replaced by an NHC or a bidentate phosphine ligand to form 3- and 4-coordinate compounds, respectively. [(I t Bu)Co(CH2 SiMe3 )2 ] (I t Bu = 1, 3-di- tert -butylimidazolin-2-ylidene) serves as an efficient, homogeneous olefin hydrogenation pre-catalyst and allows the preparation of the novel cobalt bis(alkyne) complex [(I t Bu)Co(η 2 -PhCCPh)2 ].